(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper examines the psychological aspects of human behaviour, the social ties that humans have with one another and society, and the need for humanity to grow as a sentient being to coexist harmoniously with other living forms in the universe in Octavia E. Butler’s Mind of My Mind. This novel centres on one of Doro’s daughters, Mary, who is a young, courageous biracial woman. Mary is the result of thousands of years of labour and is Doro’s near success. Her shift from a latent to an active telepath causes her to inadvertently establish a pattern, which ensnares six peculiar youths. They support her and come together as a family despite their initial animosity. They work together to gather in need individuals who are both latent telepaths and active telepaths. The figure hits one thousand and five hundred and two years later. Doro is forced to stop her endeavour because she perceives Mary’s growing authority as a threat. However, Mary disobeys, which sparks a heated argument between them. In the end, she vanquishes and destroys him with the help of the telepaths and her unbreakable will.